مساهمة النظام المحاسبي المالي في تقييم الاداء المالي في المؤسسة الاقتصادية - إيمان, خالد; عائشة, مسعودي; ابو بكر الصديق, كانش (جامعة الوادي - University of Eloued, 2023)
"الملخص يسعي النظام المحاسبي المالي إلى توفير متطلبات التقييم المالي، ويشجع على تقديم معلومات إضافية للفئات المستخدمة ويعمل على تحسين مستوى الإفصاح وجودة القوائم المالية القوائم المالية التي تم إعدادها وفق النظام المحاسبي المالي تخدم التحليل المالي وتسهل مهمة المحلل المالي حيث تهدف هذه القوائم إلى تقديم معلومات حول الوضعية المالية الميزانية، الأداء (حسابات النتائج ) تغييرات الوضعية المالية (جدول تدفقات الخزينة وجدول تغييرات الأموال الخاصة )وهو ما يتوافق مع أهداف التحليل المالي للقوائم المالية يمكن النظام المحاسبي المالي من إعداد معلومات مالية دقيقة تعكس صورة صادقة عن الوضعية المالية للمؤسسات الإقتصادية الجزائرية مما يحقق الشفافية في تقديم المعلومات التي تعتبر المدخلات الأساسية للقيام بعملية تقييم الأداء المالي وبالتالي القدرة علي تحديد نقاط الضعف والعجز ومعالجتها بغية تحقيق الأهداف المؤسسة تعتبر عملية التقييم الأداء المالي للمؤسسة علمية بالغة الأهمية وذلك لما يخدم مختلف الأطراف التي لها علاقة بالمؤسسة حيث تسمح بالحكم علي الفاعلية، وكذا تحديد الأهمية النسبية بين النتائج والموارد المستخدمة مما يسمح بالحكم على الكفاءة" "Summary The financial accounting system seeks to provide the financial evaluation requirements, encourages the provision of additional information to the categories used and works to improve the level of disclosure and the quality of the financial statements. The financial lists that were prepared according to the financial accounting system serve the financial analysis and facilitate the task of the financial analyst, as these lists aim to provide information about the financial situation, the budget, performance (results accounts), changes in the financial position (the treasury flows table and the special funds changes table), which is consistent with the objectives of Financial analysis of the financial statements The financial accounting system enables the preparation of accurate financial information that reflects an honest picture of the financial position of the Algerian economic institutions, which achieves transparency in providing information that is considered the basic input for the process of evaluating financial performance and thus the ability to identify weaknesses and deficits and address them in order to achieve the goals of the institution. The process of evaluating the financial performance of the institution is very important, as it serves the various parties that have a relationship with the institution, as it allows judging the effectivالنظام eness, as well as determining the relative importance between the results and the resources used, which allows judging the efficiency."
Keywords: النظام المحاسبي المالي ،التقييم الأداء المالي ،الإفصاح ،القوائم المالي ،التحليل المالي،المحلل المالي،تقييم الأداء; Financial accounting system, financial performance evaluation, disclosure, financial statements, financial analysis, financial analyst, performance evaluation